Impact Of Non-Debt Tax Shields On Financial Leverage: Evidence From The Malaysian Industrial Products Sector - Nashad, Mohamed (2006)
This research focuses on the impact of non-debt tax shields on leverage for firms in the Malasyian industrial products sector.